Education research and educational practice: The qualities of a close relationship. (11th May 2020) - Wyse, Dominic; Brown, Chris; Oliver, Sandy; Poblete, Ximena
Abstract : The relationship between education practice and education research has a long history. In modern times, education practice and its relation to education research has been central to debates about the nature and quality of education as an academic discipline in universities. This article reports an empirical study that investigated a new instantiation of the practice–theory debate: 'close‐to‐practice' research in education. The research sought to (a) define and further articulate the concept of close‐to‐practice research and (b) provide reflections on the quality of close‐to‐practice research. The orientation of the work reported in this article is informed by theory on traditions of knowledge in the organisation of education that have contributed to the development of education as an academic discipline. The main section of the article reports the findings of the empirical study. The research design was a rapid evidence assessment (REA), and a series of interviews with education researchers whose experiences were highly relevant to understanding of close‐to‐practice research issues. The conclusions of the research are reported in relation to how close‐to‐practice research might be defined, including in relation to quality, but also implications for education as a discipline in universities subject to nationwide assessments of quality.